Human and Murine Cell Lines for Adrenocortical Carcinoma and Pheochromocytoma - Edlira Luca; Andrea Abate; Katharina Wang; Stefan Bornstein; Sandra Sigala; Felix Beuschlein; Svenja Nölting; Constanze Hantel (Endocrines)
Adrenocortical carcinoma (ACC) and pheochromocytoma (PCC) are malignancies originating from distinct layers of the adrenal gland. ACCs arise from the adrenal cortex, are often detected at advanced stages and are associated with poor prognosis. PCCs are mostly benign, arise from the adrenal medulla and have a variable prognosis, with 10% of PCCs resulting in metastasis. Genetic background strongly influences metastasis of PCCs, and no reliable biomarkers that predict metastatic behavior exist to date. Current therapeutic strategies for both ACCs and PCCs are overall limited. Thus, novel preclinical models and drug screening approaches need to be established to aid in the identification of more promising drugs and treatment schemes. In this review, we summarize the currently available human and murine cell lines for both tumor entities.